Modeling Radionuclide Transfer from Pasture to Milk in Kisoro, South- Western Uganda - Habakwiha V; Oruru B; Tumps Ireeta W (East African Journal of Science, Technology and Innovation, 2023)
Determination of radionuclide transfer from animal feeds to animal products and ingestion transfer rates is important in assessing internal radiation risk to humans who consume the animal products. Seventy-nine (79) pasture samples and milk samples were collected from cattle farms in seven sub- counties. Activity concentrations of radionuclides in the samples were determined using gamma spectroscopy. Transfer ratios of radionuclides to from pasture to milk were calculated. Ingestion transfer rates of radionuclide from pasture to cow were also determined. Radionuclide accumulation to the body of the cow was modeled. Contributions to radiological effects due to accumulation of radionuclides in the body were estimated. Transfer ratios of uranium and thorium from pasture to milk varied from 0.07 to 0.17, and 0.05 to 0.17, respectively. The ingestion transfer rates of uranium varied from 3.1 10-6 to 7.6 10-6 y l-1 while for thorium, the ingestion transfer rates varied from 2.2 10-6 to 7.5 10-6 y l-1. The contribution to radium equivalent (Bq l-1), annual effective dose equivalent (mSv y l-1), and excess lifetime cancer Risk due to the radionuclide transfer were 0.074, 0.002, and 0.0061 10-3, respectively. Comparing with the safe values of annual effective dose equivalent in foodstuffs of 0.14 mSv y l-1 which translates to excess cancer risk of 0.42 10-3, these contributions to radiological effects only account for about 1.5% of the total safe value of excess lifetime cancer risk, therefore, radionuclide transfer from pasture to milk causes a minimal radiation hazard to the milk consumers in Kisoro District.